Burden for Parents of Patients With Schizophrenia—A Nationwide Comparative Study of Parents of Offspring With Rheumatoid Arthritis, Multiple Sclerosis, Epilepsy, and Healthy Controls. (3rd September 2018) - Mittendorfer-Rutz, Ellenor; Rahman, Syed; Tanskanen, Antti; Majak, Maila; Mehtälä, Juha; Hoti, Fabian; Jedenius, Erik; Enkusson, Dana; Leval, Amy; Sermon, Jan; Taipale, Heidi; Tiihonen, Jari
Abstract: Background: The study aimed to (1) compare the risk of health care use, adverse health status, and work productivity loss of parents of patients with schizophrenia to parents of patients with multiple sclerosis (MS), rheumatoid arthritis (RA), epilepsy, and healthy controls; and (2) evaluate such outcome measures while considering disease severity of schizophrenia. Methods: Based on linkage of Swedish registers, at least one parent was included ( n = 18215) of patients with schizophrenia (information 2006–2013, n = 10883). Similarly, parental information was linked to patients with MS, RA, epilepsy, and matched healthy controls, comprising 11292, 15516, 34715, and 18408 parents, respectively. Disease severity of schizophrenia was analyzed. Different regression models yielding odds ratios (OR), hazard ratios (HR), or relative risks (RR) with 95% confidence intervals (CI) were run. Results: Psychiatric health care use, mainly due to anxiety and affective disorders, showed a strongly increasing trend for parents of patients with schizophrenia throughout the observation period. During the follow-up, these parents had an up to 2.7 times higher risk of specialized psychiatric health care and receipt of social welfare benefits than other parents. Parents of the moderately severely ill patients with schizophrenia had higher risk estimates for psychiatric health care (RR: 1.12; 95% CI: 1.07–1.17) compared with parents of least severely ill patients. Conclusions: Parents of patients with schizophrenia have a considerably higher risk of psychiatric health care and social welfare benefit receipt than other parents. Psychiatric health care use worsens over time and with increasing disease severity of the offspring.